A metamaterial inspired multi band antenna using complementary split ring resonator for wireless applications - Reddy, Harshavardhan; Patil, Rajendra R. (Bulletin of Electrical Engineering and Informatics, 2025)
This research introduces a new printed metamaterial antenna with triple and quad bands for wireless applications. The suggested antenna is constructed of FR4 material, with two slots created in the radiating element. In addition, a circular complementary split ring resonator (C-CSRR), is carved from the ground plane. HFSS simulation software is being put into use to design, model, and measure the suggested antenna parameters in a real-world environment. The measured results indicate that an antenna with C-CSRR behind the radiating patch resonates at three distinct frequencies, including 3.5 GHz, 7.5 GHz, and 8.2 GHz, and an antenna with C-CSRR and slots on the radiating patch resonates at four different frequencies, including 3.5 GHz, 7.5 GHz, 8.8 GHz, and 9.32 GHz. An antenna without complementary split ring resonator (CSRR), or a conventional antenna, resonates at 9.6 GHz. The metamaterial antenna results in a 65% diminution in antenna size in contrast to a regular microstrip antenna. The simulated outcome demonstrates that the suggested metamaterial antenna's peak gain is around 6 dB to 8 dB and it has a resonance frequency for C-band applications, including weather radar systems and 5G applications.